Exploring the awareness of organic food consumption in Algeria: a gender based-study - Boukhedimi, Chems Eddine; Batache, Abderrahmane; Sahali, Noureddine; Redjouani, Yacine (Management and Entrepreneurship: Trends of Development, 2025)
Organic foods have greatly increased in recent years as people become more concerned about their health, the environment, and the sources of their food. These foods are produced in ways that emphasize natural processes while avoiding the use of synthetic chemicals including pesticides, fertilizers, antibiotics, and genetically modified organisms. Hence, green consumers frequently prefer organic foods for a variety of reasons, including purported health benefits, superior flavor, environmental concerns, and animal welfare. Organic foods can be more expensive than conventionally produced meals, but many people believe the advantages exceed the costs.This study has an aim to check the impact of gender of respondents on the awareness to use organic foods. This type of products is illustrated on natural milk and natural oil generated from olive. The method explored in this research is an online survey during February 11-25, 2021 among 103 Algeria participants. Then, the results were analyzed through SPSS software V26 in order to use independent samples t-test.The results indicate that the independence between the willingness to use the organic foods in order to consume organic food and the gender of respondents is ensured. It means that both men and women agree to consume it in this case (p-value = 0.296). Moreover, several suggestions were given for future studies, as well as including other variables (Age groups, academic degree, and income level).JEL Сlassification: M30, M31, D12, E21, P36